Grid Peak Shaving and Energy Efficiency Improvement: Advances in Gravity Energy Storage Technology and Research on Its Efficient Application - Shaojun Wang; Hao Xiao; Zhaoquan Zhao; Dezhao Li; Dong Hu; Qi Hu; Chen Shen; Xingyu Zhang; Jiahao Hu; Cheng Chi; Xin Cheng; Wei Zhang; et al. (Energies)
Global energy issues have spurred the development of energy storage technology, and gravity-based energy storage (GBES) technology has attracted much attention. This comprehensive review examines the principles, applications, and prospects of GBES technology, a promising solution for mitigating the intermittency of renewable energy sources and enhancing grid stability. GBES harnesses potential energy by elevating solid or liquid mediums, offering distinct advantages over other energy storage technologies such as pumped hydro storage and batteries. The study examines various GBES configurations, emphasizing the importance of system design, control strategies, and efficiency. This review also evaluates the economic, environmental, and social benefits of GBES, emphasizing its cost-effectiveness and potential for local economic growth. The need for policy support, technological innovation, and a robust regulatory framework is highlighted to promote the widespread adoption of GBES, which holds significant potential for enhancing grid stability and supporting the integration of renewable energy.